Knowledge, Perception and Management of Pre-eclampsia among Health Care Providers in a Maternity Hospital - Titilayo Olaoye, MPH; Oyewole O. Oyerinde, PhD; Oluwatoyin J. Elebuji, MPH; Oluwapelumi Ologun, BSc (Global Health and Education Projects, Inc., 2019)
Background: Morbidity and mortality of women and children associated with pre-eclampsia present major global health problems in low and middle income countries. The prevalence of pre-eclampsia in Nigeria ranges from 2% to 16.7%, with approximately 37,000 women dying from preeclampsia annually. This study examines knowledge, perception and management of preeclampsia among healthcare providers in a major maternity hospital in Lagos, southwest Nigeria. Methods: In this descriptive cross-sectional study, 110 health care providers comprising of 75 Nurses, 9 Consultant Physicians, and 26 General Medical Practitioners with varying years of service were selected using purposive sampling technique. Data were collected using a self-administered 36-item semi-structured questionnaire. Data were analysed using the Statistical Package for Social Sciences to generate descriptive and inferential statistics with level of significance set at 0.05. Results: Health care providers in the study had an average knowledge of pre-eclampsia with a mean score of 16.69±3.53. There was generally a good perception of pre-eclampsia with a mean sore of 28.31±3.71. The most-prevalent clinical management practices were emergency cesarean section (16%), magnesium sulphate infusion (29%), and fluid/electrolyte management (9%). Knowledge of pre-eclampsia and years of practice were significantly associated (F=3.31; p= 0.023). Conclusion and Global Health Implications: Gaps in the knowledge of causes, diagnoses, and treatment of pre-eclampsia may be attributable to lack of refresher trainings and absence of written practice guidelines on pre-eclampsia management. Health care providers at this hospital may benefit from training courses that include current nationally and internationally-approved management of preeclampsia. Key words: • Pre-eclampsia • Eclampsia • Knowledge • Perception • Management • Health care providers • Nigeria Copyright © 2019 Olaoye et al. This is an open-access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.